Pengaruh Literasi Keuangan dan Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi Universitas Panca Sakti Bekasi - Rahmawati, Lili; Putri, Eka (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to determine how the influence of financial literacy, and self-control on the consumptive behavior of economic education students of Universitas Panca Sakti Bekasi Class of 2020. This study used associative quantitative methods with a series of instrument tests and classical assumptions. The population of this study is economic education students in the class of 2020 with a total of 140 students. Sampling of 58 students using random sampling. Data collection method by distributing online questionnaires through google form. The data analysis techniques used are classical assumptions, multiple linear regression, and hypothesis testing with SPSS 20 software. The results of this study show (1) Financial Literacy has a significant effect on the consumptive behavior of economic education students of Universitas Panca Sakti Bekasi class of 2020; (2) Self-Control does not have a significant effect on the consumptive behavior of economics education students of Panca Sakti University class of 2020; (3) Financial Literacy and Self-Control affect the consumptive behavior of economics education students of Universitas Panca Sakti Bekasi class of 2020.